MSF Paediatric Days: a step forward in operationalising 'Humanitarian Paediatrics' - Neal Russell; Daniel Martinez; Sophie Janet; Nikola Morton; Mona Tamannai; Nadia Lafferty; Harriet Roggeveen; Oluwakemi F. Ogundipe; Inmaculada Carreras; Anja Gao; Elise Didier; Roberta Petrucci (BMJ Publishing Group, 2021)
Around the world, one in four children live in a country affected by conflict, political insecurity and disaster. Healthcare in humanitarian and fragile settings is challenging and complex to provide, particularly for children. Furthermore, there is a distinct lack of medical literature from humanitarian settings to guide best practice in such specific and resource-limited contexts. In light of these challenges, Médecins Sans Frontières (MSF), an international medical humanitarian organisation, created the MSF Paediatric Days with the aim of uniting field staff, policymakers and academia to exchange ideas, align efforts, inspire and share frontline research and experiences to advance humanitarian paediatric and neonatal care. This 2-day event takes place regularly since 2016. The fourth edition of the MSF Paediatric Days in April 2021 covered five main topics: essential newborn care, community-based models of care, paediatric tuberculosis, antimicrobial resistance in neonatal and paediatric care and the collateral damage of COVID-19 on child health. In addition, eight virtual stands from internal MSF initiatives and external MSF collaborating partners were available, and 49 poster communications and five inspiring short talks referred to as 'PAEDTalks' were presented. In conclusion, the MSF Paediatric Days serves as a unique forum to advance knowledge on humanitarian paediatrics and creates opportunities for individual and collective learning, as well as networking spaces for interaction and exchange of ideas.